Synergistic Effects of Steel Fibers and Silica Fume on the Workability, Compressive Strength, and Flexural Strength of Concrete - Kurniawan, Agus; Himawan, Lava (Fakultas Teknik Universitas Tanjungpura, 2025)
This study investigates the combined effect of steel fibers and silica fume on the workability, compressive strength, and flexural strength of concrete. Steel fiber content was fixed at 2% by weight of cement, while silica fume was incorporated at varying replacement levels of 0%, 5%, 10%, and 15% of cement weight. Workability was assessed using the slump test, while compressive and flexural strengths were measured at 28 days in accordance with Indonesian National Standards (SNI). The results indicate that silica fume content up to 15% has no significant adverse effect on workability, with all mixtures achieving slump values within the range of 8